Education for peace and peace culture in higher education : a case study of academic administrators in selected Malaysian public universities - Ahmad Zulfadhli Khairuddin (Kulliyyah of Education, International Islamic University Malaysia, 2020)
This study investigates the roles and attitudes of Malaysian academic administrators in promoting peace in higher institution. It also aims to understand how academic administrators understand peace and peace culture, the benefits and challenges faced by them to promote it. This study has employed a qualitative design, with the informants consisting of ten lecturers selected from four different universities located in Klang Valley Kuala Lumpur, Malaysia using purposive sampling technique. Utilizing in-depth semi-structured interview as a data collection method, it revealed valuable input to this study. Triangulation exercise between field notes, interviews and personal memos were carried out to establish trustworthiness and credibility of data. Thematic analysis was used and amongst the most important themes were extracted to answer all of the research questions. The findings suggested that academic lecturers' roles and attitudes were profound towards Education for Peace and their effort to spread its mission in public universities even though little is known about it. There are pre-requisites, benefits and challenges when implementing Education for Peace in higher education. The need for peace pedagogy, leadership capacity and enculturation of peace culture are indispensable to bring Education for Peace in higher education despite challenges that posed as hindrance towards the processes such as long-term planning, lack of awareness and applicability of Education for Peace in higher education. Future research is commended to observe the level of awareness on this subject for both students and lecturers.